Determinan Penerapan Health Protocol Sebagai Preventif Corona Virus Disease-19 Di Pasar Gemolong - Prita Devy (Universitas Veteran Bangun Nusantara, 2024)
This research aims to determine the determinants of implementing the Health Protocol as a preventative for Covid-19 among Gemolong Market Traders. This research is quantitative research with a cross-sectional approach. The dependent variable in this research is the implementation of health protocols, while the independent variables in the research are knowledge, perception, facilities regarding Covid-19. The research sample was taken using quota sampling with a sample size of 295 respondents who were traders selling at Gemolong Market. The analysis used by researchers to determine the influence of each variable uses multiple regression analysis. A total of 233 traders at Gemolong Market have implemented health protocols to prevent the transmission of Covid-19. The results of the research show that there is an influence of knowledge about Covid-19 on the implementation of health protocols as a preventative for Covid-19 transmission among Gemolong Market traders (p value = 0.000 < 0.05), there is no influence of perceptions about Covid-19 on the implementation of health protocols as a prevention of transmission Covid-19 among Gemolong Market traders (p value = 0.714 > 0.05) and there is an influence of the availability of Covid-19 prevention facilities on the implementation of health protocols to prevent Covid-19 transmission among Gemolong Market traders (p value = 0.000 < 0.05). Keywords: Covid-19, Facilities, Health Protocol, Knowledge, Perception